Single Anastomosis of Double Ureter Kidneys – Experience in 12 Kidney Transplant Recipients. (July 2018) - Tennak, Vladimir; Nesher, Eviatar; Eizner, Sigal; Gurevich, Michael; Mehjibovsky, Vadym; Mor, Eytan
Abstract : Introduction: Ureteral duplication is the most common renal abnormality, occurring in approximately 1%. In the transplant setting it is usually an incidental finding. The ureter-bladder anastomosis in that case can be done either separately as two single anastomosis or as one anastomosis after combining the two ureters into one opening. We sought to determine the complication rate and long-term outcome of transplanted kidneys with the single anastomosis technique for double ureter. Patients and Methods: We examined the incidence of double ureter kidney transplants using our electronic data-base. A single anastomosis technique was used in all 12 cases. We looked at the complication rate and graft survival and function at follow up. Results: The incidence of ureter duplication in our series was 1.04% (12 of 1152 transplants in adult recipients). Eight patients received a deceased donor transplant, among them 3 patients had combined pancreas-kidney transplantation and one double kidney transplantation. Another four patients transplanted with a kidney from a live-donor. The mean patient age was 48.5 years (31-67years). The mean donor age was 38.2 (9-60 years). All patients maintained their graft during the follow up (100% graft survival).There were no ureteral leak or stricture. UTI requiring hospitalization was noted in 4 patients. Conclusions: Double ureter kidney transplantation using a single anastomosis technique provides good outcome without additional risk for ureteral complications.